2021
DOI: 10.1002/jmri.28004
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Intracranial Large Artery Disease Correlates With Cerebral Small Vessel Disease

Abstract: Background Small vessel disease (SVD) shares common vascular risk factors with large artery disease (LAD). However, little is known about the relationship between intracranial artery stenosis and SVD burden. Purpose To investigate whether SVD burden correlates with severity of intracranial LAD. Study Type Retrospective. Population Five hundred and sixteen patients with LAD of arterial circulation were enrolled from one hospital, including 384 males (59 ± 11 years) and 132 females (60 ± 12 years). Field Strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Following a review of the full texts and a manual search, 21 studies were included in the meta-analyses. Of these, 14 studies were pooled to calculate the OR ( Pu et al, 2009 ; Romero et al, 2009 ; Muñoz-Cortés et al, 2013 ; Schulz et al, 2013 ; Park et al, 2015 ; Duan et al, 2018 ; Ye et al, 2019 ; Del Brutto et al, 2020 ; Fang et al, 2020 ; Benli et al, 2021 ; Yin et al, 2021 ; Choi et al, 2022 ; Huang et al, 2022 ; Wang et al, 2022 ), and seven studies were pooled to calculate the SMD ( Patankar et al, 2006 ; Chuang et al, 2011 ; Lee et al, 2011 ; Cheng et al, 2012 ; Scherr et al, 2012 ; Sahin et al, 2015 ; Ghaznawi et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a review of the full texts and a manual search, 21 studies were included in the meta-analyses. Of these, 14 studies were pooled to calculate the OR ( Pu et al, 2009 ; Romero et al, 2009 ; Muñoz-Cortés et al, 2013 ; Schulz et al, 2013 ; Park et al, 2015 ; Duan et al, 2018 ; Ye et al, 2019 ; Del Brutto et al, 2020 ; Fang et al, 2020 ; Benli et al, 2021 ; Yin et al, 2021 ; Choi et al, 2022 ; Huang et al, 2022 ; Wang et al, 2022 ), and seven studies were pooled to calculate the SMD ( Patankar et al, 2006 ; Chuang et al, 2011 ; Lee et al, 2011 ; Cheng et al, 2012 ; Scherr et al, 2012 ; Sahin et al, 2015 ; Ghaznawi et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to determine whether ICAS, similar to ECAS, is related to WMHs. To date, a considerable number of recent studies have been published investigating the correlation between intracranial and extracranial atherosclerotic stenosis and white matter hyperintensities (WMHs) ( Duan et al, 2018 ; Ye et al, 2019 ; Del Brutto et al, 2020 ; Fang et al, 2020 ; Benli et al, 2021 ; Yin et al, 2021 ; Choi et al, 2022 ; Ghaznawi et al, 2022 ; Huang et al, 2022 ; Wang et al, 2022 ). In light of this, we conducted an updated systematic review and meta-analysis to examine the potential association between ICAS or ECAS and WMHs.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. ( 2022 ) performed a retrospective study on 516 patients with intracranial atherosclerosis (ICAS) and found that there was no correlation between WMHs and the severity of large arterial stenosis. Their findings are consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, nowadays, more academics believe that there is a relationship between WMHs and large vessels in the brain. Wang et al (2022) CBV is defined as the volume occupied by intravascular blood within a particular quantity of brain tissue (including capillaries and large vessels). A drop in CBV denotes poor cerebral microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In severe ICAS patients, up to 60% have evidence of CSVD on brain MRI. 12,29 The severity of ICAS in the anterior circulation is associated with the CSVD burden. 29 Severe symptomatic ICAS patients with CSVD may have a higher risk of recurrent stroke than those without CSVD; however, this tendency was observed in the medical arm of the SAMMPRIS trial, but without a significant difference.…”
Section: Discussionmentioning
confidence: 99%